Growth and Studies of Potassium Dihydrogen Phosphate Crystals Doped With Picric Acid - Manju, T.; Selvarajan, P. (Asian Journal of Engineering and Applied Technology, 2018)
Potassium dihydrogen phosphate (KDP) crystal has been doped with picric acid to alter its physical and chemical properties. Picric acid doped KDP salt was synthesized by adding 2 mole% of picric acid into the aqueous solution of KDP. Using the synthesized salt of picric acid doped KDP and double distilled water, single crystals were grown by solution method with slow evaporation technique. The grown single crystal was subjected to XRD method to find the crystal structure. The functional groups of the sample were found by FTIR method. The elements in the picric acid doped KDP crystal were identified by EDAX and CHN analyses. SHG studies of the sample were done to check the second order NLO property. Dielectric studies for picric acid doped KDP crystal were carried out using a multi-frequency LCR meter. Thermal stability of the sample was found by TG/DTA studies. The microhardness of the sample was also measured at different applied low loads and the results obtained from the various studies are discussed.